The rationality of using DNA diagnostics in sports cardiology - A. I. Kadykova; A. V. Zholinsky; R. V. Deev (National Electronic Information Consortium (NEICON), 2023)
NGS is becoming an integral part of medical practice, including in cardiology. The role of genes in the formation of diseases of the cardiovascular system has been actively studied for the last 20 years. Currently, heart diseases with a hereditary component are usually divided into two large groups: monogenic syndromes that lead to an unfavorable outcome, including sudden cardiac death at a young age, and polygenic conditions that manifest after 35 years and are accompanied by deterioration in the quality of life. In professional sports, changes in the myocardium are almost inevitable, however, the first phenotypic signs of hereditary myocardial disease may be hidden behind adaptive changes, which are commonly called "athlete's heart". The carriage of causative genes radically changes the approach to the management of an athlete: his admission to training and competitive activities is reviewed, the volume of permissible load and the frequency of visits to a cardiologist are discussed. In this paper, we tried to identify clinical markers - «red flags» that would indicate the need for genetic testing on the example of athletes who underwent an in-depth medical examination in 2021-2022.